High efficiency Doherty power amplifier based on asymmetrical matching network - Mussa Mabrok; Zahriladha Zakaria; Tole Sutikno (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Doherty power amplifier (DPA) with high efficiency at the output power back off is highly demanded for modern wireless communication systems to achieve high data rates and reduce the power consumption and operation costs. This paper presents a new design strategy for enhancing DPA’s back-off efficiency. New design strategy called asymmetrical matching network is used to achieve asymmetric operation, which helps to compensate for the low power delivered by the peaking stage in the conventional DPA. The simulation results showed an enhancement in the back-off efficiency, where the proposed design is able toachieve 46-52% drain efficiency at 8 dB output power back-off while maintains high efficiency of 73-80 % at saturation over the designed bandwidth of 3.4-3.6 GHz. The proposed design is suitable for high efficiency sub-6 GHz fifth-generation wireless applications.